Enhancing the Character and Readability of Mission Statements in IT Startups: Implications for Stakeholder Communication and Sustainable Business Growth - Rattanapun, Supot; Thaweedech, Thikamporn; White, Alan Robert (Research in Social Sciences and Technology, 2025)
The mission statement connects vision and operations. It supports communication between organizations and stakeholders. Readability of the mission statement is important for business communication. This research examines the characteristics of mission statements. The study analyzes the readability of mission statements from several technology startup companies. The research uses Gunning’s Fog Index with data from 18 Thai technology companies listed on the Market for Alternative Investment (MAI). Counting methods are applied in the data collection and analysis process. The statistics used include frequency, percentage, mean, standard deviation, and Gunning’s Fog Index (GFI). The findings show that most mission statements contain fewer than 250 words and consist of 3 to 4 sentences. The readability level ranges from acceptable to ideal. Most readers rate the mission statements as optimal at 38.89 percent and acceptable at 33.33 percent. These two groups of businesses succeed in interacting with stakeholders to create mutual business value. Only 11.11 percent of the businesses receive ratings in the difficult category and should revise the goal statement. To support long-term growth, technology startups should prepare mission statements that show readiness in terms of customer perspectives, internal operations, financial performance, and learning and development. These findings may be useful for both businesses and stakeholders. The study is relevant to the technology industry and other sectors. The contribution to sustainable development goals remains important for economic growth and cooperation.